Expert systems in industrial engineering & an expert system design for a transportation problem - Acar, Burak (My University, 1994)
unknown
Keywords: Endüstri Mühendisliği; Genel yönetim; Uzman Sistemler (Bilgisayar bilimi); Üretim yönetimi; Yapay Zeka